1998
DOI: 10.1182/blood.v91.10.3593.3593_3593_3600
|View full text |Cite
|
Sign up to set email alerts
|

The Human Intrinsic Factor-Vitamin B12 Receptor,Cubilin: Molecular Characterization and Chromosomal Mapping of the Gene to 10p Within the Autosomal Recessive Megaloblastic Anemia (MGA1) Region

Abstract: Uptake of vitamin B12 (cyanocobalamin) is facilitated by the cobalamin-binder gastric intrinsic factor (IF), which recognizes a 460-kD receptor, cubilin, present in the epithelium of intestine and kidney. Surface plasmon resonance analysis of ligand-affinity-purified human cubilin demonstrated a high-affinity calcium- and cobalamin-dependent binding of IF-cobalamin. Complete cDNA cloning of the human receptor showed a 3597 amino acid peripheral membrane protein with 69% identity to rat cubilin. Amino-terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…[27][28][29][30] The N-terminal part of cubilin consists of 8 epidermal growth factor repeats and a 110-amino acid stretch. 25,26 Cubilin is an extracellular protein and interacts with other membrane proteins for membrane localization and endocytosis. In the proximal tubule it is believed to interact with megalin, forming a multireceptor complex with megalin driving internalization of the complex and bound ligands ( Figure 1).…”
Section: Megalin and Cubilinmentioning
confidence: 99%
“…[27][28][29][30] The N-terminal part of cubilin consists of 8 epidermal growth factor repeats and a 110-amino acid stretch. 25,26 Cubilin is an extracellular protein and interacts with other membrane proteins for membrane localization and endocytosis. In the proximal tubule it is believed to interact with megalin, forming a multireceptor complex with megalin driving internalization of the complex and bound ligands ( Figure 1).…”
Section: Megalin and Cubilinmentioning
confidence: 99%
“…1). The complete DNA sequences of rat (65), human (52), and canine (96) cubilin have been identified, showing a nonglycosylated molecular mass of 400 kDa. It has little structural homology with other known endocytic receptors.…”
Section: Cubilinmentioning
confidence: 99%
“…The posttranslational processing of cubilin may involve furin-mediated cleavage in the trans-Golgi network, as suggested by the finding that affinity-purified human cubilin appears to be truncated at a recognition cleavage site for furin in the NH 2 -terminal region (52). Furthermore, pulse-chase studies have suggested an unusual processing of cubilin in yolk sac cells, involving the expression of newly synthesized, endoglycosidase H-sensitive cubilin at the plasma membrane although the majority of cubilin is endoglycosidase H resistant (4).…”
Section: Cubilinmentioning
confidence: 99%
“…Cubam is composed of two proteins, cubilin and amnionless [He et al, 2005]. The former is a large extracellular protein of approximately 400 kDa containing 8 EGF repeats and 27 contiguous 110‐amino acid CUB domains [Kozyraki et al, 1998]. Binding of IF‐Cbl to cubam is mediated by CUB domains 5–8 of cubilin [Andersen et al, 2010].…”
Section: Introductionmentioning
confidence: 99%